Arranjos produtivos locais da indústria automobilística no estado de Goiás, Brasil - Araújo, Vanessa Marzano (2014)
The thesis has as its objective the study of Local Productive Arrangements of the Automobile Industry in the state of Goiás, as well as their contribution to regional development. The hypothesis adopted for the paper is that following the installation of the automobile industry in Goiás, there was a change to the economic dynamic of the municipalities which are part of their LPAs, with the attraction and fixation of other companies, although the Mitsubishi Motors Corporation of Brazil MMCB and Hyundai Caoa Automakers vehicles are mounted using mostly imported parts. The fact that these companies operate in complex assembly sectors induces, in differing degrees, the formation of arrangements, especially by means of the installation of companies of the auto parts and specialized services sector which can contribute to regional development. The thesis was structured in five chapters; the first chapter presents revision of the literature which makes up the theoretical and analytical framework, and themes related to regional and territorial development and construction of the LPA concept were addressed, as well as the main typologies used for its classification. The second chapter talks about the evolution of the automobile industry in Brazil, and presents indicators of income, business size, personnel employed, densification, productivity levels and average annual salary in the automobile industry in selected states and regions. The third chapter discusses the automobile industry in the State of Goiás, the spatial deconcentration and tax breaks offered to attract businesses in the sector. Following that, chapters four and five address, respectively, the LPA of the Automobile Industry of Catalão and Region and the LPA of the Automobile Industry of Anápolis and Region. The data was obtained by means of field research, and themes such as market, labor, innovation, cooperation, learning and advantages associated with the local environment, among others, were analyzed. Lastly, the paper presents the final considerations. As the main conclusion to our study, it was proved that the LPAs of the Automobile Industry formed in Catalão and region and in Anápolis and region can be classified, according to the typology proposed by Markusen (1995), as predominantly New District Industries NDI Industrial Platform Satellite, due to the tax incentives offered and also for possessing cheap labor, although they also present NDI Central-Radial characteristics, as they possess the MMCB and Hyundai Caoa Automakers acting as anchor companies. Both LPAs can be considered constructed , according to then typology proposed by Mytelka and Farinelli (2000). The LPAs, as in the typology proposed by Cassiolato and Szapiro (2003), possess governance carried out in the form of a hierarchy , with a degree of territoriality considered low , although actions seeking to improve this indicator are in the process of implantation in Catalão and region. Therefore, it is possible that Catalão and region s LPA could reach a medium degree of territoriality in the near future.